2020
DOI: 10.3390/nu12113578
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating and Moderating Effects of Physical Fitness of the Relationship between Adherence to the Mediterranean Diet and Health-Related Quality of Life in University Students

Abstract: The aim of this study was to estimate the relationship between the adherence to the Mediterranean diet (MD) and health-related quality of life (HRQoL) in university students and to assess whether this relationship is mediated or moderated by cardiorespiratory fitness (CRF) and handgrip strength. A cross-sectional study was performed involving 310 first-year Spanish university students. Adherence to the MD was evaluated with the 14-item Mediterranean Diet Adherence Screener (MEDAS), and the HRQoL was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
(94 reference statements)
3
9
0
Order By: Relevance
“…This should alert in applying strategies at both individual and community level to promote healthy dietary and lifestyle habits. Accordingly, the high consumption of the Mediterranean diet, which has been shown to protect from cardiovascular diseases (CVD) prognosis, diabetes, mortality, cancer, obesity, grant favorable health status, better biochemical profile, influence positively the quality of life the academic performance, the muscular fitness and mental health [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], may be a good way to implement healthy dietary habits, which would be easier to implement if they are joined to good sensory characteristics [ 42 ] and within the context of a healthy MedDiet.…”
Section: Discussionmentioning
confidence: 99%
“…This should alert in applying strategies at both individual and community level to promote healthy dietary and lifestyle habits. Accordingly, the high consumption of the Mediterranean diet, which has been shown to protect from cardiovascular diseases (CVD) prognosis, diabetes, mortality, cancer, obesity, grant favorable health status, better biochemical profile, influence positively the quality of life the academic performance, the muscular fitness and mental health [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], may be a good way to implement healthy dietary habits, which would be easier to implement if they are joined to good sensory characteristics [ 42 ] and within the context of a healthy MedDiet.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, the majority of people follow a Mediterranean diet, which is a healthy diet [7]. Previous research has revealed that the low adherence of Spanish university students to a Mediterranean diet is related to high alcohol consumption [5,8], smoking, low levels of physical activity (PA), living alone, and leading a sedentary lifestyle [5], and good adherence to the Mediterranean diet is associated with an improved quality of life related to perceived health [9] and low body weight [5].…”
Section: Introductionmentioning
confidence: 99%
“…Two instruments were used to assess dietary habits: (i) The Mediterranean Diet Adherence Screener (MEDAS) [56] to assess adherence to the MedDiet. This questionnaire has been adapted in different countries showing reasonable construct validity [57][58][59][60] and employed in the Spanish university population for the study of habits related to both physical and mental health [61][62][63]. The questionnaire is composed of 14 items that can score 0 (Does not meet criteria) or 1 (Meets criteria); 12 of the items refer to the frequency of consumption of certain foods (fruits, vegetables, olive oil, animal fats, red meat, nuts, industrial confectionery, fizzy drinks, wine, fish and seafood, and soft drinks) while two focus on dietary habits/characteristics consistent with a traditional MedDiet, such as preferential consumption of white over red meat and frequency of consumption related to pasta/rice/vegetables cooked with a sauce of tomato, onion, garlic, leeks sauteed in olive oil (Sofrito).…”
Section: Variables and Instrumentsmentioning
confidence: 99%